Quantification of vermicompost with nitrogen equivalence ratio on soil chemical properties and onion (Allium cepa L.) production in North Western Amhara Region Ethiopia - Addis, Zelalem; Amare, Tadele; Feyisa, Tesfaye (Food, Agriculture and Natural Resources - NETWORKS, 2024)
The experiment was conducted to determine the effects of vermicompost with equivalent nitrogen ratios on soil chemical properties and onion production in Northwestern Ethiopia. The experiment comprised six treatment levels: Control, Recommended Nitrogen, 75% Recommended Nitrogen + 25% Vermicompost, 50% Recommended Nitrogen + 50% Vermicompost, 25% Recommended Nitrogen + 75% Vermicompost, and 100% Vermicompost. These were arranged in a Randomized Complete Block Design (RCBD) with three replications. Data were analyzed using Analysis of Variance (ANOVA) via SAS software. The results showed that vermicompost combined with nitrogen affected the yield components of onions. However, soil properties, except for Total Nitrogen (TN) and Organic Carbon (OC), were not significantly affected by the treatments. The application of 50% vermicompost with 50% nitrogen resulted in the highest bulb yield (23.6 t/ha) compared to the control. Therefore, for a quick improvement in yield, applying 50% vermicompost with 50% nitrogen can be preferable in the study area and areas with similar agro-ecological conditions to achieve the highest net benefit.